Students' Understanding of Bar Graphs and Histograms: Results From the LOCUS Assessments. Issue 2 (4th May 2017) - Whitaker, Douglas; Jacobbe, Tim
ABSTRACT: Bar graphs and histograms are core statistical tools that are widely used in statistical practice and commonly taught in classrooms. Despite their importance and the instructional time devoted to them, many students demonstrate misunderstandings when asked to read and interpret bar graphs and histograms. Much of the research that has been conducted about these misunderstandings has been with students in introductory statistics classes at the college level. In this article, students in grades 6–12 completed multiple-choice and constructed-response questions about bar graphs and histograms as part of a larger study. The same misunderstandings that college-level students demonstrate were found in these younger students.